The Results of Collaborative Learning Activities Using the Jigsaw 2 Technique in Social Studies, Religion and Culture of Prathomsuksa 6 Students - Saleeon, Tipawan; Duanphensri, Rapeepat; Jaradrawiwat, Sirawan (HRD Journal, 2021)
The purposes of this research were: 1) to compare learning achievement before and after studying Social Studies, Religion and Culture subject using the cooperative learning activity with jigsaw technique II of prathomsuksa 6 students, 2) to study the collaborative ability of prathomsuksa 6 students before and after studying by using the cooperative learning activity with jigsaw technique II, and 3) to study prathomsuksa 6 students’ attitudes towards cooperative learning with jigsaw techniques II. The sample was 35 students of prathomsuksa 6 students at Watsuwannaranyikawas School. The research instruments were: 1) six cooperative learning management with jigsaw techniques II lesson plans on “Good Citizens in Democracy”, 2) the learning achievement test consisting of 30 questions, 3) the collaborative ability evaluation test, 20 items, and 4) the attitudes towards the cooperative learning activity with jigsaw technique test, 10 items. Statistics used in data analysis were mean and standard deviation and t-test dependent. The research results were found as follows; 1. Learning achievement in Social Studies Religion and Culture subject of prathomsuksa 6 students who studying with the cooperative learning activity with jigsaw technique II was higher than before studying with statistical significance at the .05 level. 2. The collaborative ability of prathomsuksa 6 students after learning by using the cooperative learning activity using jigsaw technique II was at a good level with an average score of 2.15. 3. The attitudes towards cooperative learning using jigsaw technique II of prathomsuksa 6 students after learning by using the cooperative learning activity using jigsaw technique II was at the highest level.